2020
DOI: 10.1042/bsr20191850
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA LINC00473 contributes to cell proliferation via JAK-STAT3 signaling pathway by regulating miR-195-5p/SEPT2 axis in prostate cancer

Abstract: Prostate cancer is a kind of male malignant tumor, which has brought tremendous health threat to men. Prostate cancer is difficult to be cured because of high incidence and metastasis rate. Thereby, it is of great urgency to elucidate the underlying molecular mechanism of prostate cancer for the treatment of this cancer. LINC00473 dysregulation has been observed in many cancers. However, the role of LINC00473 was unknown in prostate cancer. In the current study, we discovered that prostate cancer cells present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Meanwhile, our results illustrated that miR-195-5p was poorly expressed in prostate cancer and that its upregulation could repress prostate cancer cell proliferation, migration and invasion. Consistently, previous research has also indicated that prostate cancer cells exhibit poor expression of miR-195-5p, and that its upregulation limits cancer cell proliferation (Xing et al, 2020). The overexpression of miR-195 has been reported to markedly suppress prostate cancer cell proliferation and tube formation by downregulating proline-rich protein 11 (PRR11) expression (Cai et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…Meanwhile, our results illustrated that miR-195-5p was poorly expressed in prostate cancer and that its upregulation could repress prostate cancer cell proliferation, migration and invasion. Consistently, previous research has also indicated that prostate cancer cells exhibit poor expression of miR-195-5p, and that its upregulation limits cancer cell proliferation (Xing et al, 2020). The overexpression of miR-195 has been reported to markedly suppress prostate cancer cell proliferation and tube formation by downregulating proline-rich protein 11 (PRR11) expression (Cai et al, 2018).…”
Section: Discussionsupporting
confidence: 59%
“…Previous data suggest that SEPT2 acts as an oncogene to facilitate the development of multiple cancers, 35,36 but its role in regulating LSCC pathogenesis has not been investigated. Given that SEPT2 is significantly upregulated in both LSCC tissues and cells (Figure 1A–I), we hypothesize that SEPT2 may also promote LSCC development.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings demonstrated that LINC00473 Furthermore, Xing et al reported that LINC00473 promoted the proliferation of prostate cancer cells via JAK-STAT3 signaling pathway by regulating miR-195-5p/SEPT2 axis. 12) In another study of Bai et al, LINC00473…”
Section: Discussionmentioning
confidence: 97%